The Impact of Organizational Citizenship Behavior, Employee Engagement, and Managerial Decision-Making on the Microfinance Institutions Performance - Donni Junipriansa; Ganjar Mohamad Disastra (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
This study examines the impact of employee organizational citizenship behavior (OCB) and engagement on the performance of microfinance institutions, with a focus on the moderating role of managerial decision-making. Data were collected from 100 key microfinance institutions employees in Greater Bandung, with interviews of 10 experienced staff (>5 years) conducted to refine the questionnaire and ensure alignment with microfinance institutions work conditions. Using Structural Equation Modeling using Partial Least Squares (SEM-PLS) for data analysis, this study finds that both organizational citizenship behavior (OCB) and employee engagement significantly enhance microfinance institutions performance. The results further indicate that managerial decision-making serves as a critical mediator between OCB, employee engagement, and organizational performance. These findings underscore the importance of managerial decision-making in amplifying the effects of OCB and employee engagement on microfinance institutions performance. Furthermore, this research introduces alternative metrics for assessing OCB, employee engagement, managerial decision-making, and organizational performance.